APLIKASI SIMULASI PENILAIAN TRIDARMA PERGURUAN TINGGI DALAMPROSES SERTIFIKASI DOSEN DI POLITEKNIK NEGERI CILACAP (Infotekmesin, 2018)
The confession of professionalism can be stated in the form of sertificate awarding to lecturer bycompetent institutions. The best effort that needed for comitting certified lecturer until it is tried to be able to increase the quality of state polytechnic of Cilacap because of lecturer is the most important component to determine learning activity process. The lack of preparation will cause the lecturer who recommended on certified lecturer can not pass well. The simulation of intern score calculation of certified lecturer will be conducted by institution through committee of certified lecturer. This research focuses on the simulation of intern score calculation of certified lecturer which recommended. The method that used was software development method, i.e., prototyping. The finding of this research is this system can help to simulate the data of score evaluation. The committee of certified lecturer will be easy to make decision in committing certified lecturer and the calculation of automatic simulation score will decrease errors in calculating total score of certified lecturer.